Contextual moderators of the relationship between organizational citizenship behaviours and challenge and hindrance stress. Issue 3 (15th April 2014) - Ozer, Muammer; Chang, Chu‐Hsiang (Daisy); Schaubroeck, John M.
<x xml:space="preserve">Abstract</x> We studied the moderating roles of task interdependence and leader–member exchange (LMX) on the relationships between interpersonally (organizational citizenship behaviours – interpersonal [OCBIs]) and organizationally directed organizational citizenship behaviours (organizational citizenship behaviours targeted at organizations [OCBOs]) and challenge and hindrance stress perceptions. While OCBIs were more strongly related to challenge stress among employees reporting high levels of task interdependence, OCBOs were more strongly related to challenge stress among employees reporting high LMX. The same organizational citizenship behaviour (OCB)–context interactions were related to hindrance stress; as we predicted, these interaction patterns were the reverse of those observed for challenge stress. The model and findings extend research and theory concerning the potential negative consequences of OCBs, pointing to the role of social exchange context in these relationships. We discuss implications for performance management and theories of stress and well‐being. Practitioner points Informs managers about the negative consequences of OCBs and may persuade them to take into account such consequences when they encourage their employees to engage in OCBs, Helps managers understand how different types of OCBs may lead to different types of stress experiences and Shows how structural and social relationships may alleviate some of the negative consequences of OCBs.